KOHESI DAN KOHERENSI DALAM CERITA ANAK BAAZILUN YAFQIDU SANAMUHU - Diah Putri Lestari; Nurul Hidayah; Aufia Aisa (Al-Lahjah, 2021)
The purpose of this study is to provide an understanding of cohesion and coherence in a children's story entitled Baazilun Yafqidu Sanamuhu. The method used is a content analysis method with a qualitative approach. The results show that writing children's stories tends to be simple, maybe because this is a children's story, it should be made as simple as possible.